Orphans and the relational significance of birth: a response to Singh - Bobier, A. (Journal of medical ethics, 2021)
Prabhpal Singh has defended a relational account of the difference in moral status between fetuses and newborns. Newborns stand in the parent-child relation while fetuses do not, and standing in the parent-child relationship brings with it higher moral status for newborns. Orphans pose a problem for this account because they do not stand in a parent-child relationship. I argue that Singh has not satisfactorily responded to the problem.